Regional citrate anticoagulation in CVVH: A new protocol combining citrate solution with a phosphate-containing replacement fluid - Morabito, Santo (Blackwell Publishing Ltd, 2013)
Regional citrate anticoagulation (RCA) is a valid anticoagulation method in continuous renal replacement therapies (CRRT) and different combination of citrate and CRRT solutions can affect acid-base balance. Regardless of the anticoagulation protocol, hypophosphatemia occurs frequently in CRRT. In this case report, we evaluated safety and effects on acid-base balance of a new RCA- continuous veno-venous hemofiltration (CVVH) protocol using an 18 mmol/L citrate solution combined with a phosphate-containing replacement fluid. In our center, RCA-CVVH is routinely performed with a 12 mmol/L citrate solution and a postdilution replacement fluid with bicarbonate (protocol A). In case of persistent acidosis, not related to citrate accumulation, bicarbonate infusion is scheduled. In order to optimize buffers balance, a new protocol has been designed using recently introduced solutions: 18 mmol/L citrate solution, phosphate-containing postdilution replacement fluid with bicarbonate (protocol B). In a cardiac surgery patient with acute kidney injury, acid-base status and electrolytes have been evaluated comparing protocol A (five circuits, 301 hours) vs. protocol B (two circuits, 97 hours): pH 7.39 ± 0.03 vs. 7.44 ± 0.03 (P < 0.0001), bicarbonate 22.3 ± 1.8 vs. 22.6 ± 1.4 mmol/L (NS), Base excess −2.8 ± 2.1 vs. −1.6 ± 1.2 (P = 0.007), phosphate 0.85 ± 0.2 vs. 1.3 ± 0.5 mmol/L (P = 0.027). Protocol A required bicarbonate and sodium phosphate infusion (8.9 ± 2.8 mmol/h and 5 g/day, respectively) while protocol B allowed to stop both supplementations. In comparison to protocol A, protocol B allowed to adequately control acid-base status without additional bicarbonate infusion and in absence of alkalosis, despite the use of a standard bicarbonate concentration replacement solution. Furthermore, the combination of a phosphate-containing replacement fluid appeared effective to prevent hypophosphatemia.